THE INFLUENTIAL FACTORS OF SECOND LANGUAGE LEARNING FOR ADOLESCENT LEARNERS - Nopita, Dewi (Reflective, 2012)
While many discussions about learning a second languagefocus on teaching methodologies, little emphasis is given tothe influential factorsâindividual, social, and societalâthataffect studentsâ learning. These influential factors can be consideredfrom the perspective of the language, the learner, andthe learning process. This digest discusses these perspectivesas they relate to learning any second language, with a particularfocus on how they affect adolescent learners of Englishas a second language.